IN SITE NET PHOTOSYNTHESIS MEASUREMENT OF A PLANT CANOPY IN A SINGLE-SPAN GREENHOUSE - Takakura, Tadashi; Sunagawa, Haruki; Tamaki, Maro; Usui, Takae; Taniai, Naoki (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
Using newly developed sensor units that were more compact and accurate than earlier units (Takakura et al., 2009), this study was conducted to estimate the net photosynthesis of a plant canopy in a practical greenhouse during plant cultivation. Net photosynthesis and the ventilation flow rate are two unknowns in this greenhouse system, with adequate growth of bitter gourd plants. Environmental conditions related to evapotranspiration from the canopy and CO2 flux from the soil surface were measured respectively using the developed sensor units and a box-type CO2 concentration sensor. Heat flux from the soil was also measured. Two equations were solved: one for CO2 balance and one for water vapor balance. On-line monitoring of net photosynthesis is possible using simple and inexpensive sensors, but the obtained data of the canopy photosynthesis were scattered because of frequent changes in the ventilation amount. Furthermore, improved sensor units revealed that the evapotranspiration of the canopy was linearly related to net solar radiation in the greenhouse.